People Republic of China poverty reduction and regional cooperation fund annual report 2019. (Manila Asian Development Bank, 2021)
The report focuses on the technical assistance and grants provided through the PRC Fund from 1 January to 31 December 2019 and includes details on the operational performance of this support. An overview of the PRC Fund covering the background and rationale, objectives, operating principles and arrangements, and achievements is also presented. Administered by the Asian Development Bank (ADB), the PRC Fund was established in March 2005 to support poverty reduction, regional cooperation, and knowledge sharing among ADB developing member countries.
Keywords: Economic assistance; China -- Economic integration